Asuhan Keperawatan pada Ny. N dengan Halusinasi Pendengaran Melalui Terapi Menggambar di Rumah Sakit Jiwa Aceh (IJM: Journal of Multidisiplinary, 2025)
Auditory hallucinations are among the most frequently encountered positive symptoms of schizophrenia. This condition leads to alterations in sensory perception, in which patients perceive voices such as whispers or commands without any external stimulus, significantly affecting their ability to distinguish reality and diminishing their quality of life. This case study aimed to provide comprehensive nursing care for Mrs. N with auditory hallucinations through the application of implementation strategies and drawing therapy at Aceh Mental Hospital. Interventions included the implementation strategy carried out over two days and drawing therapy administered for five consecutive days or five sessions, each lasting 45 minutes. To assess auditory hallucinations, the Auditory Hallucination Rating Scale (AHRS) was utilized. The case study findings showed a decrease in AHRS scores, from 30 (severe category) before intervention to 22 (moderate category) after intervention. This result indicates an improvement in the frequency and intensity of auditory hallucinations, along with enhanced focus and calmness in the patient. Therefore, drawing therapy can contribute to reducing hallucination symptoms in patients with schizophrenia.